2010
DOI: 10.1007/s11064-010-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide (CGRP) Stimulates Purkinje Cell Dendrite Growth in Culture

Abstract: Previous reports described the transient expression during development of Calcitonin Gene-Related Peptide (CGRP) in rodent cerebellar climbing fibers and CGRP receptor in astrocytes. Here, mixed cerebellar cultures were used to analyze the effects of CGRP on Purkinje cells growth. Our results show that CGRP stimulated Purkinje cell dendrite growth under cell culture conditions mimicking Purkinje cell development in vivo. The stimulation was not blocked by CGRP8-37, a specific antagonist, suggesting the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The mechanisms underlying the effects of CGRP to promote the dendrite initiation remain to be examined. A similar stimulatory effect of the dendrite formation was recently reported in the cerebellar Purkinje cells (D'Antoni et al, 2010). It was suggested that the effects on Purkinje cell dendrite may be mediated by astrocytes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mechanisms underlying the effects of CGRP to promote the dendrite initiation remain to be examined. A similar stimulatory effect of the dendrite formation was recently reported in the cerebellar Purkinje cells (D'Antoni et al, 2010). It was suggested that the effects on Purkinje cell dendrite may be mediated by astrocytes.…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that CGRP promotes differentiation of dopaminergic neurons in the olfactory bulb and midbrain (Denis-Donini, 1989;Bürvenich et al, 1998). A recent study reported that CGRP promotes the dendrite formation of cerebellar Purkinje cells (D'Antoni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is more likely since, on the one hand, previous studies have reported maturation-dependent changes in length, number and appearance of axons and dendrites of the enteric neurons [35]. However, CGRP participates in physiological neuronal development through its involvement in the differentiation of neurons and the promotion of dendrite formation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is expressed mainly by neuronal cells and promotes astrocytic and neuronal differentiation (D'Antoni et al, 2010) and modulates the activity of glial cells (Uezono et al, 2001; Wang et al, 2009). CGRP not only promotes neurogenic inflammation in the periphery (Holzer, 1998) and brain (during headache; Durham, 2006), but also protects against inflammatory injuries, as in LPS-induced local acute inflammation (Gomes et al, 2005) or immune-mediated liver injury (Kroeger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%